Morpho-physiological and molecular characteristics of bacteria causing stalk rot disease on corn in Gorontalo, Indonesia - SURIANI SURIANI; BAHARUDDIN PATANDJENGI; AMRAN MUIS; MUHAMMAD JUNAID; HISHAR MIRSAM; MUHAMMAD AZRAI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suriani, Patandjengi B, Muis A, Junaid M, Mirsam H, Azrai M. 2023. Morpho-physiological and molecular characteristics of bacteria causing stalk rot disease on corn in Gorontalo, Indonesia. Biodiversitas 24: 1749-1758. Stalk rot disease was observed in corn in Gorontalo with typical symptoms, such as soft rot on the stalk, leaf wilting, and plant death. This study aimed to characterize the bacteria causing stalk rot disease in corn. Samples of infected plants were collected and identified morphologically, physiologically, and molecularly. The results showed that nine bacterial isolates were isolated from infected plants. All nine isolates showed positive hypersensitive responses on tobacco leaves. In comparison, only two bacterial isolates (BGO1 and BGO4) were positive on pathogenicity tests on corn. However, the BGO4 isolate caused the highest disease incidence with a faster incubation period. The BGO4 isolate was gram-negative with white-gray colored colonies. Physiological characterization of BGO4 also showed: positive catalase and indole, oxidase negative, fermentative oxidation, caused soft rot on potato, non-fluorescent, and sensitive to erythromycin. In addition, it can grow at 37-40°C and 5% NaCl, producing protease and lecithinase enzymes. The BGO4 also isolates infected rice, corn, sorghum, foxtail millet, celery, and Aloe vera. Morpho-physiology characteristics and diagnostic amplification of DNA by PCR using the Dickeya-specific primers (ADE1/ADE2) showed that the isolate belongs to the genus Dickeya. Further molecular characterization by analysis of the 16S rDNA using universal primer 27F/1497R successfully amplified the DNA band of BGO4 isolate measuring ±1300 bp. Phylogenetic analysis showed that it was in the same group as Dickeya zeae strain MS32 from Taiwan, strain DZ15SB01 (Thailand), and strain HNJF02 (China), with the coefficient of genetic distance ranging from 0.001 to 0.002. This study is the first report of D. zeae infecting corn in Gorontalo.